FROM RIVALRY TO INNOVATION: THE SPACE RACE AND ITS IMPACT ON GLOBAL PROGRESS AND ECONOMY - Abduraxmon Abdullayev (European Science Publishing, 2025)
The article explores the profound impact of the Space Race, a Cold War rivalry between the United States and the Soviet Union, on technological innovation and global economic transformation. It highlights pivotal achievements, such as Sputnik I and Apollo 11, and the advancements in satellite technology, GPS, and medical imaging driven by space exploration investments. Emphasizing the economic and societal benefits, the article reflects on how the Space Race fostered international collaboration, national pride, and groundbreaking progress. It concludes by linking the legacy of this era to modern space endeavors, including Mars missions and private sector innovations, as a testament to humanity's relentless pursuit of the unknown and its role in shaping the global future.
Keywords: Space Race, United States, Soviet Union, Cold War, Apollo 11, Sputnik I, space exploration, technological innovation, economic transformation, GPS, satellite technology, private space ventures, Mars exploration, international collaboration, global economy, NASA, Yuri Gagarin, James Webb Space Telescope, space industry, human ingenuity.